Medical Record Storage System Analysis On The Effectiveness Of Patient Services - Muchsam, Yoki; Rizkiana Muharam, Ilham (Rifa'Institute, 2021)
This study aims to determine and analyze the medical record storage system on the effectiveness of patient care at the Cikole Public Health Center. The research method used is quantitative with inferential statistical analysis techniques. Data collection techniques by means of observation, interviews and questionnaires. Cikole Lembang Public Health Center is one of the first level health care facilities. Based on observations, the storage system used is a regional storage system in which each region starts from the first digit. There are 2 officers who work in the medical records section of the Cikole Public Health Center. With the storage system used, there are several shortcomings, namely the occurrence of misfiles and duplication. To find out whether there is an analysis of the medical record storage system on the effectiveness of the service, the author gives a questionnaire to the Cikole Public Health Center officers. The results of the questionnaire also show that the highest percentage level is found in item no.7, namely the decentralized storage system is in accordance with the target of 71%. Then the second is item no. 8, namely a decentralized storage system that allows the provision of medical record files on time by 61%. From the results of interviews with medical records officers, suggestions and input were given: (1). The storage system used was changed to centralization so that the alignment system was not duplicated; (2). The use of bindex as an additional tool to make storage neater and easier.